Parental Education Level and Child Cognitive Ability: An Analysis Based on Evidence from the China Education Panel Survey - Liu, Jindian; Cheng, Mingwang; Wu, Chunyan (Best Evidence in Chinese Education, 2025)
Drawing on the data from the China Education Panel Survey, the article investigates the effects of parental education level on child cognitive ability using descriptive statistics and quantitative analysis. Research findings of the study reveal that parental education level is significantly and positively related to child cognitive ability, with a greater impact on the cognitive ability of girls than boys, and that its effects on the child’s cognitive ability decline as the latter improves. The analysis of mediation effects shows that parental education level affects child cognitive ability via its impact on home educational expectations and investment.